Deletion of NADPH oxidase 2 attenuates cisplatin-induced acute kidney injury through reducing ROS-induced proximal tubular cell injury and inflammation - Chen, Ho-Ching; Hou, Hsin-Yu; Sung, Junne-Ming; Shieh, Chi-Chang (Frontiers in Medicine, 2023)
Cisplatin is a commonly used chemotherapeutic agent in cancer treatment. However, its high nephrotoxicity limits its therapeutic application and efficacy. Cisplatin induces nephrotoxicity mainly through oxidative stress and inflammation. Reactive oxygen species (ROS) in the kidneys mainly arise from nicotinamide adenine dinucleotide phosphate (NADPH) oxidases 2 (NOX2), which is highly upregulated during ischemia-reperfusion injury and diabetes mellitus. However, its role in cisplatin-induced acute kidney injury (AKI) remains unknown. We investigated the role of NOX2 in cisplatin-induced AKI and found that NOX2-mediated ROS production is a key inflammatory mediator of proximal tubular cell injury in cisplatin-induced AKI. NOX2 gene-knockout alleviated cisplatin-induced renal function decline, tubular injury score, kidney injury molecule-1(Kim-1) expression, and interleukin (IL)-6 and IL-1α levels with a reduction of ROS production. Moreover, in cisplatin-induced AKI, intercellular adhesion molecule 1 (ICAM-1) and the chemoattractant CXC ligand 1 (CXCL1) were highly expressed in association with neutrophil infiltration, which were all attenuated by deletion of NOX2. These data indicate that NOX2 aggravates cisplatin nephrotoxicity by promoting ROS-mediated tissue injury and neutrophil infiltration. Thus, appropriate targeting of NOX2/ROS pathway may minimize the risk of cisplatin-induced kidney injury in patients receiving cancer therapy.